Adult-onset Repeat Rhabdomyolysis with a Very Long-chain Acyl-CoA Dehydrogenase Deficiency Due to Compound Heterozygous ACADVL Mutations - Takahashi, Makio; Sakurai, Takeyo; Sato, Kei; Kaji, Seiji; Nishino, Ichizo; Fukuda, Tokiko; Sugie, Hideo; Fuseya, Yasuhiro; Miyahara, Jun-ichi; Saito, Yoshihiko; Yamashita, Hirofumi (Internal Medicine, 2020)
Very long-chain acyl-CoA dehydrogenase (VLCAD) deficiency is a genetic disorder of fatty acid beta oxidation that is caused by a defect in ACADVL, which encodes VLCAD. The clinical presentation of VLCAD deficiency is heterogeneous, and either a delayed diagnosis or a misdiagnosis may sometimes occur. We herein describe a difficult-to-diagnose case of the muscle form of adult-onset VLCAD deficiency with compound heterozygous ACADVL mutations including c.790A>G (p.K264E) and c.1246G>A (p.A416T).